Antibacterial Activity of Bacterial Pigment Extracts Isolated From Fruit and Vegetable Waste Against Staphylococcus epidermidis - Salsabila, Haniya; Maharani, Andrea; Siregar, Abdul Rahman (Al-Kauniyah: Jurnal Biologi, 2025)
Acne affects approximately 9.4% of the global population and become one of the big eight skin diseases due to Staphylococcus epidermidis infection. This infection can be treated using bacterial pigments for their potential activities as antioxidant, anticancer, and antimicrobial with low toxicity and stable productivity. In this study, pigments were harvested and purified from pigment-producing bacteria which were isolated from fruit and vegetable waste, and the antibacterial activity was conducted with disc diffusion method against S. epidermidis. There were three pigment-producing isolates (LBS 6, LBS 12, and LBS 14) that produced green pigments with antibacterial activity against S. epidermidis. Among the pigments produced by the three isolates, pigments from LBS 14 had the widest zone of inhibition and the strongest antibacterial activity followed by LBS 6 and LBS 12 respectively. In addition, through Two-Way ANOVA analysis, it was found that there was a significant effect on the utilization of pigments from different bacterial isolates and variations in concentration on the diameter of the inhibition zone as well as the interaction between them